2018
DOI: 10.1186/s12943-018-0888-8
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA microarray profiling identifies a novel circulating biomarker for detection of gastric cancer

Abstract: CircRNA expression profiles for gastric cancer (GC) were screened using plasma samples from 10 GC patients with different TNM stages and 5 healthy individuals as controls. Results showed lower expression of circ-KIAA1244 in GC tissues, plasmas, and cells compare to normal controls. Further clinical data analysis demonstrated that a decreased expression of circ-KIAA1244 in plasmas was negatively correlated with TNM stage and lymphatic metastasis, and a shorter overall survival time of GC patients. Moreover, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
163
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(165 citation statements)
references
References 6 publications
2
163
0
Order By: Relevance
“…Therefore, circulating tumor circRNAs (ct circRNAs) can be applied as potential signatures for the diagnosis of cancer. Tang et al (13) had demonstrated that plasma circ-KIAA1244 might be a potential signature in patients with GC. As far as we know, however, there are few studies on circRNAs in the plasma of patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, circulating tumor circRNAs (ct circRNAs) can be applied as potential signatures for the diagnosis of cancer. Tang et al (13) had demonstrated that plasma circ-KIAA1244 might be a potential signature in patients with GC. As far as we know, however, there are few studies on circRNAs in the plasma of patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…9 In gastric cancer, circ-KIAA1244 is correlated with cancer progression and patients' outcome. 10 In non-small cell lung cancer, hsa_circ_0033155 acts as a tumour suppressor to regulate cell proliferation, colony formation and migration. 11 However, there are only a few reports exploring circRNAs in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicated that circRNAs act as potential biomarkers in patients with GC. Upregulation of circ-DON-SON, circAKT3, and circDLST [8,11,13] or downregulation of KIAA1244, circPSMC3, and circFAT1(e2) [14][15][16] is regarded as independent prognostic factors of poor prognosis in patients with GC. Herein, we identified a novel circDUSP16, and it was resistant to RNase R and localized in the cytoplasm of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…CircAKT3 and circDLST act as the sponges of miR-198/-502-5p to favor the tumorigenesis and cisplatin resistance in GC cells [11,13]. In addition, circ-KIAA1244 [14], circPSMC3 [15], and circFAT1(e2) [16] are downregulated in GC tissues and plasmas, and their decreased expression is related to tumor invasiveness and poor survival in GC patients [14][15][16]. These circRNAs may provide potential biomarkers for the treatment of GC.…”
Section: Introductionmentioning
confidence: 99%